EKSISTENSI FESTIVAL OF LIGHTS AS A TOURISM ICON SLEMAN HOUSING - Santosa, Santosa (Sekolah Tinggi Pariwisata AMPTA, 2016)
ABSTRACT Studies on the existence of an activity is the same as searching for findings about community opinion against discussing the activity. Qualitative research shaped aims to find the opinions of the public about the conduct of the Festival of Lights as an icon of Sleman Regency tourism Organisations. Study of the results of research to prove the eksistnsi of the Festival of Lights includes aspects of promotion, the process of organizing, comfort and appeal activities show that being able to suck a lot of visitors and most of the people who made the research respondents agree and give a positive response (good). With regard to the results of such research could be recommended that such events can be followed up to the coming times KeyWord : Festival of Lights, Tourism Icon.